The Effect Mnure And Concentration Of Em-4 DoseOn Plant Growth And Yield Of RedSpinach (Alternanthera Amoena Voss) - Martha Junita Doodoh; Sri Hidayati; Nurlina (Agricultural Science, 2017)
The purpose of the study to determine the effect of various doses of manure on the growth and yield of red spinach. Randomized Factorial Experiment is used with three replications. The first factor is the dose Manure P1 = 5 tons/hectare; P2 = 10 ton/ hectare; P3 =Dose manure 15 t / ha. The second factor is the concentration of EM-4, among others K1 = dose of 5 ml/liter of water/polybag; K2 = dose of 10 ml/liter of water/polybag; K3 = dose of 15 ml/liter of water/polybag. Of the two factors 9 combination treatments are obtained which was then repeated 3 times. There was no significant interaction at F5% test level on all variables studied i.e plant height, leaf number and gross weight per plant at all age of observation. There were significant effects of manure dose factor studied, mainly on plant height variables, number of leaves and gross weight per plant; and statistically, a better value in all of these variables is achieved by treatment P3 manure dose of 15 ton/ha. EM-4 concentration factor has significant influence on plant height variables, number of leaves and gross weight per plant; statistically, a better value in all of these variables are also achieved by treatment of the K3 of 15 ml/liter of water/polybag.